A new conservative numerical integration algorithm for the three-dimensional Kepler motion based on the Kustaanheimo–Stiefel regularization theory - Minesaki, Yukitaka; Nakamura, Yoshimasa (Physics letters. A, 2004)
A new conservative numerical integration algorithm for the three-dimensional Kepler motion is presented which conserves all of the constants of motion including the Runge–Lenz vector. The Kustaanheimo–Stiefel regularization theory plays a central role in the discretization of the equations of motion.